DEVELOPMENT OF ANALYTICAL METHOD FOR IMATINIB MESYLATE BY ULTRAVIOLET SPECTROSCOPY - AJITHKUMAR P; ANTON SMITH A (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: A simple, selective, sensitive, specific, and spectrophotometric method has been developed for the detection of imatinib mesylate in pure form and formulations. Methods: The analytical condition was optimized for the drug, carried out as per the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use guidelines. Results: The drug shows absorption at 232.0 nm and obeyed beers law in the wide concentration range from 0.5 to 4.0 μg/ml. The lower limit of detection was found to be 0.331 μg/ml and the limit of quantification to be 1.004 μg/ml. The regression equation was found to be y = 0.08x. The precision of the method was found to be 99.04%±0.527% and the percentage of drug recovered by this method is 100.13%±1.375%. Conclusion: The method is simple and suitable for determination for imatinib mesylate in pure and pharmaceutical preparation.